Thrombotic thrombocytopenic purpura: Description and analysis of 23 cases treated in Chile between 2017 and 2022 - Daniel Cathalifaud; Jean-Paul Manríquez; Benjamín Rodríguez; Gonzalo Eymin; Benjamín Sanfuentes; Joel Castellano; Andrés Valenzuela (Medwave)
Introduction Since the first description of Thrombotic Thrombocytopenic Purpura, caused by a severe deficiency of ADAMTS13, plasma exchange and immunosuppression have become standard treatments, allowing to decrease its high mortality rate. Prospective records of Thrombotic Thrombocytopenic Purpura have provided valuable information on its pathophysiology, clinical presentation, and outcomes. The objective of this study is to update the local Chilean experience in the diagnosis and management of this disease, through a case series of patients treated between 2017 and 2022.